Overcoming Of Aggressive Behavior Of Primary School Children Through Fairy Tale Therapy - Mikaelian, Marine; Muradyan, Manushak (Զանգակ հրատ.)
The article provides definitions of aggression, the causes of its occurrence, as well as fairy tale therapy as a means of overcoming aggressive manifestations. A research was conducted to study the psychological characteristics of the aggressive behaviour of younger schoolchildren. The formative linear experiment was used. The method for diagnosing aggression Bass-Darky and Rosenzweig's test of measuring the aggressiveness were carried out. In the aggressive behavior of primary school children is dominated by negative and indirect aggression; verbal and physical aggression are moderately manifested; auto-aggression, insult and suspicion are weakly expressed. More than half of primary schoolchildren have a high level of aggressiveness. In the vast majority of pupils, aggressive reactions are directed to the environment, that is, the orientation of aggression is extrapunitive. In about a quarter of pupils, the orientation of aggression is impunitive, for what happened they attribute the blame to the situation. The weakest expression has the intrapunitive orientation of aggression, when the child considers himself responsible for the event. To overcome the aggressive manifestations of primary schoolchildren, a training program was used, in which therapeutic tales and training exercises were included. If before applying a training program for overcoming agressiveness, aggressive reactions of most younger schoolchildren were directed at others, and they considered others to be responsible for solving the problem, then after implementing the training program the results of the retest show that there has been a sharp increase in the rate of intrapunitive aggression. That is, children began to count, that the solution of the problem depends more on the person, and in case of failure, the person should blame not the other, but own identity. Therapeutic fairy tales are an effective way to overcome the aggressive behaviour of children in educational institutions.
Keywords: Psychology